2015
DOI: 10.3390/ijerph13010021
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for Compliance to Breast, Colorectal, and Cervical Screening Cancer Tests among Hispanic Patients

Abstract: Hispanics are less likely to undergo screening tests for colorectal cancer and cervical cancer than non-Hispanic whites. Compliance with mammography, fecal occult blood testing (FOBT), colonoscopy, and cervical smears (PAP) and barriers for compliance were studied. A descriptive study was performed with 194 ambulatory patients while they attended routine medical visits. Women are more likely than men to undergo a colonoscopy. Conversely, FOBT was most likely reported by men. Reasons for compliance with FOBT di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Moreover, they are at higher risk of infection-related cancers such as stomach and liver ( 16 ). Determinants of health that contribute to this disparity include low rate of medical insurance coverage ( 17 , 18 ), lack of knowledge about services ( 19 ), scarce availability and access to genetic counseling ( 20 ), limited access to and use of cancer screening programs ( 9 , 21 , 22 ), poverty, neighborhood socioeconomic status, ( 23 , 24 ) and other complex sociocultural and geographic factors, such as living in an ethnic enclave ( 25 27 ). Distinct from non-Hispanic whites, Siegel et al ( 28 ) reported cancer as the leading cause of death for Hispanics, surpassing heart disease ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are at higher risk of infection-related cancers such as stomach and liver ( 16 ). Determinants of health that contribute to this disparity include low rate of medical insurance coverage ( 17 , 18 ), lack of knowledge about services ( 19 ), scarce availability and access to genetic counseling ( 20 ), limited access to and use of cancer screening programs ( 9 , 21 , 22 ), poverty, neighborhood socioeconomic status, ( 23 , 24 ) and other complex sociocultural and geographic factors, such as living in an ethnic enclave ( 25 27 ). Distinct from non-Hispanic whites, Siegel et al ( 28 ) reported cancer as the leading cause of death for Hispanics, surpassing heart disease ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…And yet, a number of barriers to cancer screening have been identified, including cost, fear, trust, time and lack of knowledge [1013]. These barriers have been highlighted as a major contributor to the lower cancer screening rates for Latinas and Black/African American women [1416], and higher mortality rates for certain cancers, including breast and colon, among Black/African American women [17] and cervical among Latinas [18]. …”
Section: Introductionmentioning
confidence: 99%
“… 14 Similarly, others note that the main reason why many Hispanic women avoid mammography is because of fear, busy schedules, and also feeling uncomfortable during the screening procedure. 15 In contrast, various studies have indicated that fear can motivate routine screening for cancer and that worry about breast cancer risk appears to be associated with mammography use in an inverted u-shaped pattern in which most of the women who reported moderate levels of worry were more likely to use mammography annually than those who were either mildly or severely worried. 16 Another study revealed that self-regulation and cancer worry were both positively associated with mammography screening and clinical breast examination frequency.…”
Section: Introductionmentioning
confidence: 99%